Breastfeeding practices among lactating mothers of a rural area of central India: a cross-sectional study - Junaid, Mohd; Patil, Sachin (International Journal Of Community Medicine And Public Health, 2018)
Background: Breastfeeding is an unequalled way of providing ideal food for the healthy growth and development of infants. As per national family health survey-3 (NFHS-3), only 46% of the Indian infants between 0 and 6 months are exclusively breastfed. Hence the following study was done to know the practice of breastfeeding in mothers of rural area of central India. Methods: The study was conducted in a rural area, which is under administrative control of tertiary care hospital. All lactating mothers having babies upto 1 year were included in study. An informed written consent was obtained from the mothers. Results: 78.28% show initiation of breastfeeding within 6 hours of delivery. 51.51% mothers breastfeed child whenever they cry and 35.35% breastfeed every 2 hourly. Exclusive breastfeeding was practiced by 58.58% mothers and 64.15% mothers gave first breast milk to their newborns. Conclusions: The counseling should be continued after the delivery of baby for continuous education to mother about the proper care of newborn, initiation of breastfeeding, the information regarding the advantages and duration of breastfeeding, importance of colostrums feeding, timing of weaning needs to be provided.